Uji Aktivitas Antibakteri dan Sitotoksik Ekstrak Metanol Aglaia silvestris (M.Roemer) Merr. - Praptiwi, Praptiwi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
The antibacterial and sitotoxic activities of ganggo (Aglaia silvestris (M.Roemer) Merr. methanol extract were determined in this study. Antibacterial in-vitro test of ganggo methanol extract was exposed to Gram positive (Staphylococcus aureus ATCC 25923, Streptococcus agalactiae ATCC 8190, and Streptococcus sp.) and Gram negative (Salmonella typhii NCTC 786 E, Eschericia coli ATCC 25922, and Pseudomonas pseudomallei ATCC 15682) bacteria. The extract concentrations were 50, 25 and 12.5%, and done in triplicate. The growth inhibition area of extract was compared to those of standard antibiotic (10 unit ampicilin). Cytotoxic test of ganggo extract was done utilizing Brine Shrimp Lethality Test (BST) with Artemia salina.The result showed that growth inhibition area of 12.5% ganggo methanol extract to P. pseudomallei (19 mm) was wider than that of 10 unit ampicilin (0 mm). It showed that P. pseudomallei was sensitive to ganggo methanol extract. The result of BST showed that LC50 of ganggo extract was 345.44 ppm. It was concluded that ganggo methanol extract had antibacterial effects on some bacteria isolates and had cytotoxic effects with LC50 345.44 ppm.